Synthesis and application of modified membranes for efficient cationic and anionic dye elimination - Meriem Mansour Hafifi; Abdelkader Chougui; Mohammed Amin Chemrak; Aissa Belouatek (The Journal of Engineering and Exact Sciences)
This study focuses on developing ceramic ultrafiltration membranes using locally sourced kaolin clay and feldspar. An active layer composed of graphene and alkoxide is added to enhance the performance of these clay supports. This layer is thin, porous, and can vary in thickness. The support and filter layer's porous properties are characterized using SEM, DRX, ATG/ATD, XPS, and FTIR techniques. Filtration tests are conducted on modified porous tubular supports using cationic and anionic dye solutions. The filtration is performed tangentially at a pressure of 3.5 bar and a processing time of 120 minutes. The retention rates of the colored solutions are measured using a UV-visible spectrophotometer. The results show a 100% retention rate for supranol yellow and orange II at a concentration of 10-4 M, while for crystal violet and malachite green, the retention rates are 92.03% and 95.30%, respectively.